Q. 6 D3.5( 13 Votes )

# If <span lang="EN

a + b = a + b = = = = 3

a-b = a-b = = = = √5

ab = = 1

(a + b)3 = a3 + b3 + 3ab(a + b)

a3 + b3 = (a + b)3 - 3ab(a + b)

= (3)3 – 3 × 1 × 3

= 27 – 9 = 18

(a-b)3 = a3-b3-3ab(a-b)

a3-b3 = (a-b)3 + 3ab(a-b)

= (√5)3 + 3 × 1 × (√5)

= 5√5 + 3√5

= √5 [5 + 3]

= 8√5 Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses RELATED QUESTIONS :

In each of the foWest Bengal Board - Mathematics

If <span lang="ENWest Bengal Board - Mathematics

Let us write a raWest Bengal Board - Mathematics

Let us rationalizWest Bengal Board - Mathematics

Let us write the West Bengal Board - Mathematics

Let us write whetWest Bengal Board - Mathematics

Let us fill up thWest Bengal Board - Mathematics

Let us divide firWest Bengal Board - Mathematics

The product of <sWest Bengal Board - Mathematics

Let us write the West Bengal Board - Mathematics